Factors Associated with Early-Stage Diagnosis of Oral and Pharyngeal Cancer - Ubaidullah, Huma Tahir, Liaqat Ali, Burhan Samad, Muhammad Tahir, Zarak Khan, Hamaila Saeed, Laiba Asif, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Oral cancer is still being identified at advanced stages, reducing patients' odds of surviving. Oral and pharyngeal cancer (OPC) has the highest rate of death and morbidity among oral illnesses. The present study aimed to determine the factors associated with early-stage diagnosis of oral and pharyngeal cancer. Materials and Methods: This interview based survey was conducted on 112 newly diagnosed OPC patients at Dentistry Department of Tertiary Care Hospital, Rawalpindi from July 2020 to December 2020. Those patients with lip’s malignancies, oral cavity, or oropharynx were eligible. A patient with recurring tumors in the hypopharynx or nasopharynx and a patient with nasopharyngeal malignancies were excluded from the study. Patient’s characteristics such as early or advance stage of cancer, pattern of dental care, and occurrence of early signs and symptoms were compared and analyzed. Details regarding patient’s utilization of dental care such as primary care on regular basis and the latest dental visits by OPC examination receipt were recorded. Data analysis was done using SPSS version 27. Results: Of the total 112 OPC patients, there were 76 (67.9%) male and 36 (32.1%) females. Based on smoking status, the incidence of current, former, and never smoked participants were 40 (35.7%), 38 (33.9%), and 34 (30.4%) respectively. The prevalence of Oral cancer screening during the most recent dentist appointment were 23.8% (n=27). The proportion of patients with a frequent primary healthcare dentist 64% (n=72) was higher than the proportion of patients without a primary healthcare dentist 36% (n=40). The likelihood of undergoing an OPC examination was significantly influenced by the frequency of dental primary care, dentistry appointments in the past 12 months, and regular treatment. Most patients reported discomfort in their mouth as their first symptom, which was influenced by the disease stage at diagnosis. Conclusion: The present study found that individuals who had an OPC exam were far more prone to be identified at an earlier and more curable stage. Despite this, only a relatively small proportion of those newly diagnosed with OPC reported that they had recently received an OPC exam. OPC examinations were more likely to be performed on regular dental treatment participants than episodic use participants, nevertheless even among frequent attendees, there were numerous missed chances. These findings highlight the need of dental practitioners doing frequent OPC exams on all patients, including episodic attendees. Keywords: Early-stage diagnosis, Oral and pharyngeal cancer, oral pathology